Kebijakan Satu Data Indonesia: Tantangan Dan Peluang Pengambilan Keputusan Publik - Pratiwi Lukman, Juwita; Fiulaizi, Anna (stiatabalong.ac.id, 2026)
Digital government transformation requires integrated data governance as the foundation for evidence-based public decision-making. The Satu Data Indonesia policy, enacted through Presidential Regulation No. 39 of 2019, was designed to address inter-agency data fragmentation through data standardization, interoperability, and data-sharing mechanisms. This study aims to analyze the implementation of the Satu Data Indonesia policy and to identify its opportunities and challenges in supporting national-level public decision-making. The research employs a qualitative approach using policy analysis and literature review of regulatory frameworks, official government documents, and relevant national and international scholarly articles. Data were analyzed through descriptive analysis and thematic synthesis. The findings indicate that the implementation of the Satu Data Indonesia policy has progressed in terms of regulatory framework and institutional strengthening at the central government level, although its implementation remains uneven across regions due to disparities in digital infrastructure capacity, data quality, and human resources. At the same time, the policy creates significant opportunities to strengthen evidence-based policymaking through cross-sectoral data integration, improved bureaucratic efficiency, and enhanced policy transparency. From an implication perspective, successful implementation has the potential to advance a transition toward more transparent, accountable, and data-driven governance, provided that persistent challenges related to data fragmentation and inter-agency coordination are systematically addressed